2017
DOI: 10.1186/s13065-017-0243-y
|View full text |Cite
|
Sign up to set email alerts
|

Purification, characterization and procoagulant activity of polysaccharides from Angelica dahurice roots

Abstract: Five polysaccharides, namely ADPs-1a, ADPs-1b, ADPs-2, ADPs-3a and ADPs-3b, were extracted from Angelicae dahuricae Radix, purified, and identified by high performance gel permeation chromatography (HPSEC), gas chromatography (GC), Fourier transform infrared (FT-IR) spectrometer and nuclear magnetic resonance spectra (NMR), including the determination of procoagulant activity in vitro. The average molecular weight (Mw) of the polysaccharides was 153,800, 8312, 111,700, 3766 and 96,680 g/mol, respectively. Coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 1 publication
(1 reference statement)
0
9
0
Order By: Relevance
“…The four polysaccharide fractions were further purified by Toyopearl-H65F gel resin (1.6 × 80 cm) and eluted with 0.2 mol/l NaCl at a flow rate of 0.5 ml/min [16, 17]. Then the solution was collected in accordance with four elution peaks (DOP-40, DOP-50, DOP-60, and DOP-70), concentrated, and dialyzed against distilled water for 48 h, fresh distilled water was replaced every 4 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The four polysaccharide fractions were further purified by Toyopearl-H65F gel resin (1.6 × 80 cm) and eluted with 0.2 mol/l NaCl at a flow rate of 0.5 ml/min [16, 17]. Then the solution was collected in accordance with four elution peaks (DOP-40, DOP-50, DOP-60, and DOP-70), concentrated, and dialyzed against distilled water for 48 h, fresh distilled water was replaced every 4 h, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…First, the derivatives (hydrolysis and acetylation) of PCp-I and PCp-II were carried out, and monosaccharide compositions were then analyzed by Gas Chromatography (GC, GC-2010, Shimadzu, Japan) equipped with a HP capillary column (30 m × 0.35 mm × 0.25 μm, Aglient Technologies, Inc., PaloAlto, Santa Clara, CA, USA) and a FID detector using the published method [49]. The standard monosaccharides (glucose, xylose, arabinose, rhamnose, mannose, ribose, fructose, and galactose) were derivatized and subjected to GC analysis in the same way.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study, we found that several polysaccharides have coagulation or anticoagulation activities [9][10][11][12]. Up to date, there is no research on the coagulation effect of the F. velutipes polysaccharides.…”
Section: Introductionmentioning
confidence: 97%